LETâ€™S SPEAK UP : PELATIHAN PUBLIC SPEAKING â€œPEMUDA PEMBENTUK PERADABAN DI ERA MILLENIALâ€ - Diah Ayu Septi Fauji; Ismayantika Dyah Puspasari (Universitas Kadiri, 2019)
The development of Indonesia in the future depends on the role of the youth. But now many young people are still embarrassed to speak in public (public speaking), therefore it takes practice on public speaking. The theme of this training is